Manajemen Pendidikan Entrepreneur dalam Meningkatkan Kompetensi Wirausaha Santri pada Pondok Pesantren Riyadlusharfiwalmantiq - Udin Nawawi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
This study aims to determine the implications of planning, implementing and evaluating entrepreneurial education on the entrepreneurial competence of students at the Riyadlusharfiwalmantiq Islamic Boarding School. The research method uses a qualitative approach with phenomenological methods, data collection techniques using observation, interviews and documentation techniques. The analysis technique uses SWOT analysis. The validity test used source training and technical triangulation methods. The results of the study indicate that the Entrepreneurship Education plan at the Riyadlusharfiwalmantiq Islamic Boarding School is set out in the form of an entrepreneur learning curriculum, which consists of theory-based learning planning and practice-based planning. Furthermore, it is described in the form of a learning syllabus that contains basic competencies, subject matter, indicators, learning activities, time allocation and assessment. Entrepreneurship education is implemented with two methods, namely theory-based learning and practice-based learning. Evaluation of the results of Entrepreneurship Education is carried out in 2 ways, directly (during the learning process) and post-learning. To examine the evaluation of entrepreneurial education learning using an evaluation model, namely the evaluation of the CIPP (Context, Input, Process, and Product) model. Entrepreneurial competence of students at Riyadlusharfiwalmantiq Islamic Boarding School was formed to have social entrepreneur and corporate entrepreneur competencies. Entrepreneurial education management has implications for students to gain knowledge, skills, and attitudes and aims to make students have the ability and ability to become beginners in entrepreneurship.